Transcriptome analyses indicate that heat stress-induced inflammation in white adipose tissue and oxidative stress in skeletal muscle is partially moderated by zilpaterol supplementation in beef cattle. (25th January 2022) - Reith, Rachel R; Sieck, Renae L; Grijalva, Pablo C; Swanson, Rebecca M; Fuller, Anna M; Diaz, Duarte E; Schmidt, Ty B; Yates, Dustin T; Petersen, Jessica L
Abstract: Heat stress (HS) triggers oxidative stress, systemic inflammation, and disrupts growth efficiency of livestock. β-adrenergic agonists supplemented to ruminant livestock improve growth performance, increase skeletal muscle mass, and decrease carcass fat. The objective of this study was to understand the independent and interacting effects of HS and zilpaterol hydrochloride (ZH) supplementation on the transcriptome of subcutaneous white adipose tissue and the longissimus dorsi muscle in steers. Twenty-four Red Angus-based steers were assigned to thermoneutral (TN; Temperature Humidity Index [THI] = 68) or HS (THI = 73–85) conditions and were not supplemented or supplemented with ZH (8.33 mg/kg/d) for 21 d in a 2 × 2 factorial. Steers in the TN condition were pair-fed to the average daily feed intake of HS steers. RNA was isolated from adipose tissue and skeletal muscle samples collected via biopsy on 3, 10, and 21 d and sequenced using 3ʹ Tag-Seq to an achieved average depth of 3.6 million reads/sample. Transcripts, mapped to ARS-UCD1.2, were quantified. Differential expression (DE) analyses were performed in DESeq2 with a significance threshold for false discovery rate of 0.05. In adipose, 4 loci ( MISP3, APOL6, SLC25A4, and S100A12 ) were DE due to ZH on day 3, and 2 ( RRAD, ALB ) were DE due to the interaction of HS and ZH on day 10 ( P adj < 0.05). In muscle, 40 loci (including TENM4 and OAZ1 ) were DE due to ZH on day 10, and 6 loci ( HIF1A, LOC101903734, PDZD9, HNRNPU, MTUS1, and TMCO6) were DE due to environment on day 21 ( P adj < 0.05). To explore biological pathways altered by environment, supplement, and their interaction, loci with DE ( P raw < 0.05) were evaluated in Ingenuity Pathway Analysis. In adipose, 509 pathways were predicted to be altered ( P < 0.01): 202 due to HS, 126 due to ZH, and 181 due to the interaction; these included inflammatory pathways predicted to be upregulated due to HS but downregulated due to the interaction of HS and ZH. In muscle, 113 pathways were predicted to be altered ( P < 0.01): 23 due to HS, 66 due to ZH, and 24 due to the interaction of HS and ZH. Loci and pathway data in muscle suggest HS induced oxidative stress and that the stress response was moderated by ZH. Metabolic pathways were predicted to be altered due to HS, ZH, and their interaction in both tissues. These data provide evidence that HS and ZH interact to alter expression of genes in metabolic and immune function pathways and that ZH moderates some adverse effects of HS. Lay Summary: Heat stress (HS) negatively impacts livestock health and carcass quality. Supplementation of livestock with β-adrenergic agonists (β-AA) increases muscle mass and decreases fat deposition. The purpose of this study was to understand how HS and zilpaterol hydrochloride (ZH), a β-AA, alter gene expression in muscle and in adipose of cattle. Twenty-four steers were assigned to thermoneutral (TN) or HS conditions and were not supplemented (NS) or supplemented with ZH for 21 d. RNA was isolated from muscle and adipose collected on days 3, 10, and 21 to identify changes in gene expression. Several individual loci were differentially expressed (DE) due to HS or ZH in both tissues while the interaction of HS and ZH altered expression in adipose. A less stringent definition of DE used to explore biological pathways predicted that both treatments alter metabolism. Pathway analyses also supported that HS increased inflammation in adipose, but that these inflammatory pathways were downregulated by ZH. HS also was predicted to induce oxidative stress in muscle although ZH moderated this response. This study provides information on how HS and β-AA act independently and interact to alter physiology, lending insight useful for the development of management and mitigation strategies for stress. Abstract : Transcriptomic evidence supports that heat stress induces stress pathways in adipose and muscle of cattle. Pathway analyses support that supplementation of zilpaterol hydrochloride to heat-stressed cattle moderates some of the unwanted impacts of heat stress.